Students’ attitudes toward ESP course at university level - Ivančević Otanjac, Maja (Specijalna edukacija i rehabilitacija, 2021)
Introduction. English for Specific Purposes (ESP) at universities has a challenging goal of meeting the needs of usually large and heterogeneous groups of students. Objective. The aim of this study was to examine students’ attitudes toward the ESP course, acquired knowledge, and course materials at the Faculty of Special Education and Rehabilitation, University of Belgrade. In addition, the study examined the possible influence of students’ general English proficiency on the tested variables. Methods. An online questionnaire was used to collect data from 75 students who completed the ESP course in 2020 or 2021. Their general English proficiency was assessed by an online general English test. Results. The results showed that most students were satisfied with the acquired professional English language knowledge and available course materials and that their attitudes toward the completed ESP course were not influenced by their general English proficiency. Conclusion. These results are encouraging since they indicate overall student satisfaction with the ESP university course taught to a large class.
Keywords: ESP; general English; course materials; technical vocabulary; special education